The Impact of Using the Analytical Procedure Methods in Preventing the Risks of Statistical Samples in Auditing, A Study According to Auditing Standards (520, 530) - Mohammed Ali Hassan (Harmoni Economics: International Journal of Economics and Accounting, 2025)
Purpose: The study's aim to highlight how the relationship between the auditing standard Analytical Procedures (520) and reducing audit sample risks, a study according to the standard of auditing (530), and the complementary role between them. The sample chosen for the community matches the financial operations after a thorough assessment using analytical methodologies to gain reasonable certainty that the information presented in the financial statements and management report is reliable, fair, and unbiased. Theoretical framework: The theoretical framework of the study included introductory frameworks for analytical procedures in terms of the concept, objectives and methods they contain, as well as introductory frameworks for the concept of audit samples, their risks and the factors influencing their size, as well as the theoretical relationship between the impact of analytical procedures on audit samples. Design/methodology/methodology: In order to accomplish the aims of the study, the focus was on the inductive approach by highlighting the impact of the relationship to the standard of auditing for analytical procedures (520) in preventing the risks of audit samples, a study according to the standard of auditing (530), and the complementary role between them, And the impact and then the transition to the general path by generalizing the results that have been reached. Also, the deductive approach was relied on to strengthen definitional frameworks for the independent variable, analytical procedures, and the dependent variable, audit samples, through what is contained in books, theses, and scientific research, identifying the general aspects, and delving into the results of the practical side of the study. Findings: The results of the statistical analysis showed the following the existence of a significant relationship between the impact of the methods of analytical procedures in preventing the risks of statistical samples in the audit process. It measures either the significance level (Sig. F) of the model as a whole is (0.000), which is less than (5%) hypothesized by the researcher and should be analytical The analysis accepts the hypothesis of the model that there is a significant effect relationship between the utilization of the analytical procedures approach in the reduction of statistical sampling risk in the audit study based on auditing standards (520, 530).